Behavioral analysis of a captive male Bornean orangutan (Pongo pygmaeus) when exposed to environmental changes - Larsen, Josefine F.; Andersen, Karl K. D.; Cuprys, Julia; Fosgaard, Thomas B.; Jacobsen, Johanne H.; Krysztofiak, Dominika; Lund, Silje M.; Nielsen, Birgitte; Pedersen, Maja E. B.; Pedersen, Matilde J.; Trige-Esbensen, Adam; Walther, Emilie M.; et al. (Archives of Biological Sciences, 2023)
Paper description: The requirements of captive Bornean orangutans (Pongo pygmaeus) and the advantages of enrichment are well comprehended. The exploration of post-relocation adaptation and the effects of mixed-species habitats on animal welfare is substantiated. The study examined a relocated male orangutan at Aalborg Zoo, Denmark, observing behavioral changes post-relocation and upon introducing small-clawed otters, using recorded behavior and ethograms. Stress-related behaviors were decreased after the introduction of otters, suggesting improved welfare. These findings contribute towards a better understanding of captive orangutan behavior and the value of mixed-species habitat for enhanced welfare, emphasizing the significance of enrichment. Abstract: Understanding the species-specific behavioral needs of Bornean orangutans (Pongo pygmaeus) has led zoological gardens to focus on creating more natural and stimulating facilities. Studies have documented enhanced welfare through various methods, including environmental enrichment like mixed-species habitats, which could improve animal welfare. This study aimed to evaluate the behavioral adaption following the transfer to a new facility and the possible effects of environmental enrichment on an orangutan in captivity at Aalborg Zoo in Denmark. A newly arrived male was observed for analyzing behavioral changes in the weeks after relocation and introducing two small-clawed Asian otters (Aonyx cinereus) to the facility. Changes in behavior were analyzed using recorded behavior and an ethogram before and after the introduction of the otters. The expression of behaviors associated with stress and individual plasticity was analyzed, and the results indicated a change in the behavioral phenotype in response to the introduction of the otters. The study shows that behaviors associated with stress decreased after the introduction of small-clawed otters, suggesting that it had a positive effect on the behavior of the orangutan.